Analisis Implementasi Permendikbud Ristek Nomor 46 Tahun 2023 Tentang Pencegahan dan Penanganan Kekerasan Bullying di Lingkungan SMP Negeri 2 Medan - Nisa Andriani Regar; Majda El Muhtaj; Ramsul Nababan; Parlaungan Gabriel Siahaan; Arief Wahyudi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
This study aims to analyze the role and challenges of the Violence Prevention and Handling Team (TPPK) in implementing the Regulation of the Minister of Education, Culture, Research, and Technology (Permendikbud Ristek) Number 46 of 2023 at SMP Negeri 2 Medan. The research employed a qualitative descriptive method with an empirical juridical approach through observation, interviews, and documentation. The results indicate that the TPPK has performed its role quite effectively in preventing, handling, and recovering from cases of violence, particularly verbal and non-verbal bullying. These efforts are manifested through socialization activities, character education, student behavior guidance, and the strengthening of communication among schools, teachers, and parents through class association groups. However, the implementation of this policy still faces several challenges, such as the low awareness among students regarding the impacts of verbal bullying and the limited involvement of some parents in mediation and guidance processes. Overall, the TPPK is considered to be on the right track in policy implementation; nevertheless, there is a need to strengthen educational and collaborative strategies to ensure that the policy can be carried out more effectively and sustainably.